HERPES SIMPLEX KERATITIS IN A TERTIARY CARE CENTRE: A CLINICAL PRESENTATION - GOMPA MOHANA PREETHI; DIKSHA PANCHBHAI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objectives of the study are (1) to evaluate the demography of herpes simplex keratitis and (2) to determine the incidence of various forms of herpes simplex keratitis. In developing countries, bacterial and fungal keratitis are the most common cause of keratitis. Hence, the epidemiology of herpes simplex keratitis is not well studied. The present study aims to study the epidemiology of herpes simplex keratitis. Methods: It is a prospective study of herpes keratitis patients at a tertiary care center. The study was conducted on 50 patients who presented in the tertiary care center from January 1, 2021, to August 30, 2021. Detailed history, slit-lamp examination, fluorescein staining, corneal sensations, and other needful investigations were carried out. The diagnosis was made clinically. Results: Males (60%) were affected more than females (40%). Most of the patients were between the ages of 30 and 50. The order of most common presentation is epithelial keratitis (60%), stromal keratitis (34%), endotheliitis (4%), and mixed stromal and epithelial keratitis (2%). The majority of the patients had mild visual impairment (60%). Conclusion: Herpes simplex keratitis presented mostly in the 3rd–5th decade. In comparison to females, it is more common among males. The order of presentation observed was epithelial keratitis followed by stromal keratitis followed by endotheliitis followed by mixed stromal and epithelial keratitis. The majority of the patients presented with mild visual impairment.